Electronic Accounting Information Systems and Their Role in the Development Quality of the Internal Auditing by Computer - Osman, Rania Noureldin; Al-Mougtaba, Mohamed Al-Moutaz (Journal of Economic, Administrative and Legal Sciences, 2019)
This research addressed Electronic Accounting Information Systems and Their Role in the Development Quality of the Internal Auditing by Computer. So the main problematic of this research is keen to raise the following questions did the relationship between the application of the electronic accounting system and the quality of the performance of the internal audit process? Does the use of the computer in the internal audit process affect the quality of the accounting information? The aim of the research is to identify the electronic accounting information systems, to know the impact of the electronic accounting information systems, on the internal audit, and to devaluate the extent of the use of references. To achieve the objective of the study was the use of the curriculum. On the formulation of hypotheses scientific research and use the tow researchers the questionnaire as tool to collect data. Which reflect the views sample analysis research which was cruising through the use of the program SPSS. The researcher to prove the validity of hypotheses linking variables. Electronic Accounting Information Systems impact is positive and on the Development Quality of the Internal Auditing.